Breastfeeding and nutrition habits of 0-24 month infants in a semi-urban region of Manisa - Berna Bilgin Şahin; Beyhan Cengiz Özyurt (Turkish Society of Public Health Specialists, 2017)
Objective: The aim of this study is to evaluate the breastfeeding habits of 0-24 month infants.  Method: This study is descriptive and aims to reach the whole reference population without using any sampling methods. The study was conducted on 140 mothers with 0-24 month-old babies, all registered in a Family Health Center in a semi-urban region of Manisa. Results: It was found that 96.4% of the mothers breastfed at least once. The first nutrition given after birth was breast-milk in 87.9% of the cases, and 56.4% of infants were fed with only breast-milk for the first six months. The average breastfeeding duration was 8.5±6.2 months.  55.6% of infants were introduced to supplementary food after six months, where 72.3% of the supplementary food provided was milk or milk products. The likelihood of the infants only breastfeeding in the first six months had a statistically significant relationship with the parents' education levels and the father's employment status. The median duration of breastfeeding had a statistically significant relationship with the mother's age, the age difference with a previous child, and with whether or not the infant experienced a lower respiratory tract infection in the first 6 months of life. Conclusions: The parents having at least a secondary school education, the father being employed in the upper social classes, the mother's age being at or more than 30, and a greater than 2 year difference between children were all found to be positive factors for both the presence and duration of breastfeeding. Key words:  Breast milk, Breastfeeding, 0-24 month infants